Improved Particle Swarm Optimization Algorithm for Hydrothermal Generation Scheduling - Yadav, Deepika; Naresh, R.; Sharma, Veena (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
The short term hydrothermal scheduling (STHTS) problem is a complicated nonlinear dynamic constrained optimization problem, which plays an important role in the economic operation of electric power systems. The objective of hydro thermal generation scheduling is to minimize the overall operation cost and to satisfy the given constraints by scheduling optimally the power outputs of all hydro and thermal units under study periods, given electrical load and limited water resource. This paper presents an improved particle swarm optimization (IPSO) algorithm for solving the STHTS problem considering valve point loading for fixed head hydro-thermal system. Various other heuristic algorithms such as basic PSO, modified PSO, differential evolution, real variable genetic algorithm (RVGA) are also implemented on the same problem. The programs for these algorithms have been developed in Matlab software. From the simulation results, it is found that the IPSO based approach is able to provide a better solution at a lesser computational effort. DOI: http://dx.doi.org/10.3126/hn.v15i0.11298 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 15, 2014, July Page: 65-72